BEX2 is required for maintaining dormant cancer stem cell in hepatocellular carcinoma. Issue 11 (4th September 2021) - Fukushi, Daisuke; Shibuya‐Takahashi, Rie; Mochizuki, Mai; Fujimori, Haruna; Kogure, Takayuki; Sugai, Takahiro; Iwai, Wataru; Wakui, Yuta; Abue, Makoto; Murakami, Kazuhiro; Nakamura, Yasuhiro; Yasuda, Jun; et al.
Abstract: Cancer stem cells (CSCs) are responsible for therapy resistance and share several properties with normal stem cells. Here, we show that brain‐expressed X‐linked gene 2 (BEX2), which is essential for dormant CSCs in cholangiocarcinoma, is highly expressed in human hepatocellular carcinoma (HCC) lesions compared with the adjacent normal lesions and that in 41 HCC cases the BEX2 high expression group is correlated with a poor prognosis. BEX2 localizes to Ki67‐negative (nonproliferative) cancer cells in HCC tissues and is highly expressed in the dormant fraction of HCC cell lines. Knockdown of BEX2 attenuates CSC phenotypes, including sphere formation ability and aldefluor activity, and BEX2 overexpression enhances these phenotypes. Moreover, BEX2 knockdown increases cisplatin sensitivity, and BEX2 expression is induced by cisplatin treatment. Taken together, these data suggest that BEX2 induces dormant CSC properties and affects the prognosis of patients with HCC. Abstract : BEX2 is essential for dormant cancer stem cell and affects patients' prognosis in hepatocellular carcinoma. BEX2 could be a promising therapeutic target.